The Enlightenment Scale: Further Evidence for Validity. Issue 2 (November 2015) - Boyd Wilson, Belinda; Walkey, Frank
Abstract : The purpose of this study was to find further evidence for the validity of the Enlightenment Scale, a measure that has two factors: At Peace and Open-Hearted. The scale was designed to measure the simple experience of enlightenment. Enlightenment is essentially a way of being and is difficult to define in scientific terms; however, it can be said to involve the complete surrender of the separate self, and to be characterized by qualities such as authenticity, living in the moment, compassion, and a sense of wholeness and inner peace — although not necessarily the absence of pain. Further evidence for the validity of the scale was sought through replication of its factor structure and through investigations into associations between its scores and those on the key predictor variables: Mindfulness and Self-Enhancement Bias. The results largely supported the predictions made. A confirmatory factor analysis performed on an independent data set showed that the two-factor structure of the scale replicated, and there was a strong correlation particularly between At Peace and Mindfulness scores but also between Open-Hearted and Mindfulness scores. There was no relationship between Self-Enhancement Bias and At Peace scores, and Self-Enhancement Bias dropped as Open-Hearted scores rose above low levels. By contrast, Self-Enhancement Bias rose as Mindfulness rose from medium to high levels. Thus, the results provide further evidence of the incremental and construct validity of the Enlightenment Scale. Possible limitations of the study and future research directions are discussed.